2008
DOI: 10.1111/j.1365-2567.2007.02713.x
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell subsets in lymph nodes are characterized by the specific draining area and influence the phenotype and fate of primed T cells

Abstract: Dendritic cells (DC) are important in differential T-cell priming. Little is known about the local priming by DC in the microenvironment of different lymph nodes and about the fate of the imprinted T cells. Therefore, freshly isolated rat DC from mesenteric lymph nodes (mLN) and axillary lymph nodes (axLN) were phenotyped and cultured with blood T cells in the presence of the superantigen Mycoplasma arthritidis mitogen (MAM). The phenotype, proliferation and apoptosis of the primed T cells were analysed. Our d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…One type of these highly motile cells are the DC, which migrate from the draining area into the LN. DC from mLN can be distinguished from those from pLN by their different subset composition and expression pattern of surface molecules (e.g., CD103) (21,22). The results showed that DC from pLNtx had been replaced by DC with a subset composition and phenotype typical for mLN, underlining the generally accepted observation that the DC came from the drained area.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…One type of these highly motile cells are the DC, which migrate from the draining area into the LN. DC from mLN can be distinguished from those from pLN by their different subset composition and expression pattern of surface molecules (e.g., CD103) (21,22). The results showed that DC from pLNtx had been replaced by DC with a subset composition and phenotype typical for mLN, underlining the generally accepted observation that the DC came from the drained area.…”
Section: Discussionmentioning
confidence: 83%
“…After activation, T cells and also B cells acquire a gut-homing phenotype, including high CCR9 and ␣ 4 ␤ 7 integrin expression (17)(18)(19)(20). Furthermore, DC from the mLN differ from those in pLN in their ability to imprint T cells in the direction of Th2 (7,(21)(22)(23), e.g., IL-4 is found at a higher concentration in the mLN compared with the pLN (24). However, it is not known whether this unique microenvironment is due to the highly motile components of the mLN or to stromal cells.…”
Section: Ymph Nodes (Ln)mentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, different from TILs that occurred in tumor tissue where there is tumor-induced immune suppression and lacks functional antigen-presenting cells (APCs), the T cells within MDLN occurred in a microenvironment where functional APCs and relevant cytokines present. 10 Thus, tumor antigen encounter occurred in MDLNs may have resulted in the generation of antigenspecific T cells. 11 This has been demonstrated in murine models that lymph nodes draining progressively growing tumor contain antigen-specific T cells capable of mediating protective immune responses.…”
mentioning
confidence: 99%
“…Focusing on mobile immune cells, gut DCs were found to be positive for CD103 3 and they preferentially expressed the retinal dehydrogenases RALDH2. 4 Furthermore, DCs from mesenteric LN (mLN) differed from those in peripheral LN (pLN) in their ability to imprint T cells in the direction of T helper type 2 (Th2), for example, interleukin (IL)-4 was found at a higher concentration in the mLN compared with the pLN.…”
Section: Introductionmentioning
confidence: 99%